Data on trend changes of drinking groundwater resources quality: A case study in Abhar - Yousefi, Mahmood (Data Brief, 2018)
The data of this study was to determine the groundwater quality trend changes in Abhar city (Iran) during one decade (2002–2016). In the first and end year of the study period, the Mean±SD of total hardness (as calcium carbonate, mg/l), electrical conductivity (as micromhos/cm) and total dissolved solid in the first and end year of the study period were 192.69±56.83, 235.25±84.73 and 606.21±194.69, 744.55±288.52 and 348.79±106.81, 464.71±183.52 respectively. On the basis of Pearson correlation coefficient, the ascending trend of some parameters concentration with time was significant at the level of 95% of confidence limits (α ≤ 0.05).